The SCAFFOLDING AND INVESTIGATION OF THINKING TO CALCULUS PROJECT IN PROJECT BASED LEARNING (PBL) ACTIVITIES - Zaini, Zaini (Universitas Mulia, 2021)
PBL adoption is increasingly widespread and recognized for various disciplines in higher education and in basic education has made a trend in learning innovation today. PBL provides individual freedom to find, utilize, build knowledge through experience in the form of project completion. The characteristics of the project used are the existence of investigations that give students the freedom to change and build knowledge. The investigation took place every day in a row from the student team (2 people) for 4 days for the given calculus project. The results of project completion investigations were delivered through team presentations, discussions, interviews with lecturers, and the provision of scaffolding by lecturers.Investigation which success include combination, definition of maclaurin series, tribe and series and derivative function which support project finishing, describing material supporting of project through example,verification binomial theorem, identification to 30 tribes maclaurin series/binomial series and approach value through tool of conting/ software(excel,calculator,geogebra) Scaffolding thinks incompatibility occurs in understanding and interpretation of combination notation, thought theorem, and implementation in calculations. Researcher's discovery that students are very active in building knowledge and exploring their experiences, as well as building openness in teams and instructors.